2010
DOI: 10.1074/jbc.m109.097964
|View full text |Cite
|
Sign up to set email alerts
|

Diadenosine Homodinucleotide Products of ADP-ribosyl Cyclases Behave as Modulators of the Purinergic Receptor P2X7

Abstract: ADP-ribosyl cyclases from both vertebrates and invertebrateswere previously shown to produce two isomers of P1,P2 diadenosine 5,5؆-P1, P2-diphosphate, P18 and P24, from cyclic ADP-ribose (cADPR) and adenine. P18 and P24 are characterized by an unusual N-glycosidic linkage in one of the adenylic mononucleotides (Basile, G., Taglialatela

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
17
0
1

Year Published

2012
2012
2019
2019

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 12 publications
(19 citation statements)
references
References 49 publications
1
17
0
1
Order By: Relevance
“…One example is that of the diadenosine diphosphate isomer P18, which both antagonizes P2X7 and activates P2Y 11 [14,81], demonstrating the need to test possible P2Y 11 agonistic and antagonistic compounds on all ATPbinding P2 receptors before drawing any conclusions about specificity.…”
Section: Selective P2y 11 Activation and Inhibitionmentioning
confidence: 99%
“…One example is that of the diadenosine diphosphate isomer P18, which both antagonizes P2X7 and activates P2Y 11 [14,81], demonstrating the need to test possible P2Y 11 agonistic and antagonistic compounds on all ATPbinding P2 receptors before drawing any conclusions about specificity.…”
Section: Selective P2y 11 Activation and Inhibitionmentioning
confidence: 99%
“…Using pharmacological inhibitors and siRNA technology, we demonstrated that the high [Ca 2+ ] i levels of the SC from CMT1A rats are causally determined by PMP22-related overexpression of the P2X7 purinoceptor, which is responsible for enhanced influx of extracellular Ca 2+ [Nobbio, 2009]. The addition of extracellular P18, at a 200 nM concentration, was able to downregulate the basal [Ca 2+ ] i levels of SC from CMT1A rats to values comparable to those measured in wild type SC [Bruzzone, 2010]. Thus, the activity of P18 and P24 as P2X7 modulators may be of potential therapeutic significance with different possible applications, in which targeting (either inhibiting or stimulating) P2X7 might prove a successful strategy.…”
Section: Other Topological Problems Related To Cd38 Productsmentioning
confidence: 77%
“…Indeed, in HEK293 stably transfected with P2X7, micromolar P24, but not P18, elicits the opening of P2X7 and the consequent slow and enhanced entry of extracellular Ca 2+ [Bruzzone, 2010]. Remarkably, both P24 and P18 proved to inhibit, with an IC 50 of 17.0 and 1.0 M, respectively, the ATP-induced [Ca 2+ ] i elevation and the consequent pore formation of P2X7.…”
Section: Other Topological Problems Related To Cd38 Productsmentioning
confidence: 95%
See 1 more Smart Citation
“…In addition, P2Y11 is the only purinergic receptor coupled to both AC and phospholipase C [Qi et al, ]. We demonstrated that P18 behaves as an antagonist of P2X7 [Bruzzone et al, ]. Unlike P18, P24 is a partial agonist of P2X7, eliciting influx of extracellular Ca 2+ , without leading to pore formation [Bruzzone et al, ].…”
mentioning
confidence: 99%